Understanding the monitoring practices of teleworkers in the public sector in Malaysia - Othman, Nafishah; Abd Wahab, Alawiyah; Mat Yusof, Sharmila; Sheik Osman, Wan Rozaini (2017)
Purpose - The concept of teleworking or telecommuting is known as working away from the traditional brick and mortar office at anytime and anywhere through utilizing ICT tools to link workers to their main office.In practice, Malaysia has started implementing the teleworking arrangement especially in multinational corporations. However, the implementation is not widely spread in the nation because majority of the Malaysian organizations do not officially acknowledge the concept of teleworking (Rafidah et al., 2006).The most common issue among managers who manage teleworkers is the loss of control over their subordinate’s daily job activities (Davis, 2011).On the other hand, employees are concerned with the issue of violation of workplace privacy and decreased opportunity for jobs promotions. There have been many studies that focuses on monitoring strategies of teleworkers and organizations in the western context (Kurlan and Egan, 1999; Fairweather, 1999). However, the strategies for monitoring Malaysian teleworker could be different as people in Malaysia are integrated into cohesive in-groups with collective tendencies (Ndubisi, 2004).Thus, the objective of this research is to explore the monitoring requirements and to identify the practices of monitoring teleworkers in Malaysian government organization.This research is based on a case study of Jabatan Kerja Raya (JKR) or Public Works Department where the results are mainly based on the practices of teleworking at JKR. Organizational Control theory has been used as a framework in achieving the objectives of the study.Three types of controls that are output, behaviour and clan are being examined and confirmed that all those controls are required in monitoring teleworkers.